On Art and Artists: An Anthology of Diderot's Aesthetic Thought - Diderot, Denis. author. aut Link
VIII, 189 p.
Keywords: Chance ordained that Denis Diderot was not only a philosopher, playwright and writer, but also a salonnier. In other words, an art critic. In 1759, his friend Grimm entrusted him with a project that forced him to acquire “thoughtful notions concerning painting and sculpture” and to refine “art terms, so familiar in his words yet so vague in his mind. Diderot wrote artistic reviews of exhibitions – Salons – that were mounted bi-annually by the Académie Royale de Peinture et de scultpure. These reviews, published in the Correspondence littéraire, were Diderot’s unique contribution to art criticism in France. He fulfilled his task of salonnier on nine occasions, despite misgivings of his own enthusiasm and self-confidence. Compiled and presented by Jean Seznec, this anthology helps the contemporary reader to familiarize himself with Diderot’s aesthetic thoughts in all its greatness. It includes eight illustrations and is followed by texts from Jean Starobinski, Michel Delon, and Arthur Cohen. On Art and Artists has been edited and translated by John S.D.Glaus who is an amateur dix-huitièmeiste. His current project is the translations of the remaining Diderot Salons.